Quantitative HPLC analysis of gallic acid in benincasa hispida prepared with different extraction techniques - Fatariah, Z.; Tg. Zulkhairuazha, T.Y.; Wan Rosli, W.I. (Universiti Kebangsaan Malaysia, 2014)
Ash gourd (Benincasa hispida, Bh) is traditionally claimed useful in treating asthma, cough, diabetes, haemoptysis and hemorrhages from internal organs, epilepsy, fever and balancing of the body heat. One of the major phenolic acids presented in Benincasa hispida is gallic acid, a phenolic compound which is linked with its ability in reducing Type II diabetes. The aim of the present study was to investigate the effect of different extraction techniques on the concentration of gallic acid in Bh. The Bh extracts were prepared with three different techniques namely; fresh extract (FE), low heating (LH) and drying and heating (DH). The gallic acid has been detected and quantified using high performance liquid chromatography (HPLC) coupled with UV-Vis detector. The amount of gallic acid detected in FE, LH and DH were 0.036, 0.050 and 0.272 mg/100 g, respectively. The limits of detection was 0.75 μg/mL while the limit of quantification and recovery were 2.50 μg/mL and 95.53%, respectively. In summary, HPLC technique coupled with UV detector systems able to quantify gallic acid in Bh extracts. The gallic acid were present at higher concentration in Bh extracted using drying and heating, followed by low heating and fresh extract methods.